Extended Attribute Grammars - Watt, David A. (DAIMI Report Series, 1981)
Two new formalisms are introduced: extended attribute grammars, which are capable of defining completely the syntax of programming languages, and extended attributed trans!ation grammars, which are additionally capable of defining their semantics by translation. These grammars are concise and readable, and their suitability for language definition is demonstrated by a realistic example. The suitability of a large class of these grammars for compiler construction is also established, by borrowing the techniques already developed for attribute grammars and affix grammars. Revised version of Glasgow Report No.10